Cannon Fire : A Life in Print. - Cannon, Michael (Melbourne University Publishing, 2022)
Michael Cannon is best known as the author of landmark and popular works of Australian history, including The Land Boomers (1966), and as the founding editor of Historical Records of Victoria. But Cannon, the child and grandchild of important figures in Australian independent journalism, developed a fascination with print media early in his life and had a long and colourful career in printing, publishing and editing books, newspapers and magazines. In Cannon Fire he brings to life many notable personalities with whom he worked, including Keith and Rupert Murdoch, and recreates the ink-stained, cigarette-smoke-filled and always well-lubricated worlds of publishing across Melbourne and Sydney in the second half of the twentieth century. More than this, Cannon's intimate account of a life that began in the 1920s fascinates as both a personal story of unusual courage in the face of challenge and heartache, and as a tale of times now passing from memory.